Predominant frequency of HLA‐B*27 in patients with ankylosing spondylitis in southeastern China - JiaoJiao Lu; Jing Yang; WenXu Dong; BaoJia Tang; LuoYuan Cao; YingHua Lin; BaoYing Huang; XianGuo Fu (Immunity, Inflammation and Disease)
Abstract Objectives This study was to investigate the polymorphism and distribution of alleles of HLA‐B*27 in patients with ankylosing spondylitis (AS) in Han population of southeastern China. Methods A total of 89 peripheral blood samples from southeastern Chinese Han patients with AS that diagnosed according to Modified New York criteria were subtyped using the high‐resolution PCR‐SSP.Exon 2‐3 of HLA‐B*27 gene was amplified and sequenced to further confirm the HLA‐B*27 subtype. Results The frequency of HLA‐B*27 was 99.87% in AS patients. Three subtypes, HLA‐B*2704, HLA‐B*2705, and HLA‐B*2706 were identified. The frequencies for these three alleles were HLA‐B*2704 in 84/88 (95.46%), HLA‐B*2705 in 3/88(3.41%), and HLA‐B*2706 in 1/88 (1.13%) of the HLA‐B*27 positive patients, respectively. Conclusions Our study shows that HLA‐B*2704 has an overwhelming frequency in southeastern Chinese Han AS patients. A combined analysis including previous studies of HLA‐B*27‐subtype distributions in Chinese Han populations showed that HLA‐B*2704 may originate from the southern Han and then migrate and spread to the northern areas, and HLA‐B*2705 show the opposite result.